PWE-110 What is the significance of "diminutive" colonic polyps in patients screened for colon cancer after a positive faecal human haemoglobin test (FHH)?. (28th May 2012) - Mahesh, V; Lim, A; Pietris, K; Argyrides, J
Abstract : Introduction: By definition "diminutive" colonic polyps are ≤5 mm in size. Improvements in optical imaging modalities and image resolution coupled with increased operator awareness have resulted in a higher detection rates at colonoscopy. Although such polyps are low risk for malignancy, studies suggest that high grade dysplasia may occur up to a rate of 4% in these polyps. There is an ongoing debate regarding the natural history and prognostic relevance of these polyps including suggestions for non-resection/to resect and discard. Aim: To analyse the significance of "Diminutive" colonic polyps in patients screened for colon cancer after a positive Faecal Human Haemoglobin test. Methods: Patients referred to a single tertiary institution in South Australia for screening colonoscopy after detection of a positive FHH. All patients referred between 2007 and 2010 were included in this retrospective study. The patients were referred either through the National Bowel Cancer Screening Program (NBCSP) or through GP initiated screening. Polyps were measured after the tissue was placed in formalin (histological size). For each colonoscopy the predetermined aim was to resect all polyps and assess histologically. Results: A total of 384 patients had colonoscopy. NBCSP referred (n=173, 45%) and GP initiated FOBT (n=211, 55%). 228 M: 156 F with mean age of 61.8±0.6 yrs, 305 polyps in total. Majority of the polyps (57%, n=173) were ≤5 mm compared with 6–9 mm (23%, n=69; p<0.001) and ≥10 mm polyps (21%, n=63; p<0.001). The histological features of the polyps ≤5 mm were predominantly tubular adenomas (TA) (80%, n=86/107), please see Abstract PWE-110 table 1 for rest of histology. Only 38% (n=66) of polyps ≤5 mm were hyperplastic in nature. In polyps ≤5 mm in size, one TA with high grade dysplasia (0.6%) was seen but no carcinoma compared to 11 (3.6%) carcinomas/high grade dyspasia in ≥6 mm size polyps (p<0.001). Three cancers were seen, two in polyps ≥10 mm size and one in the 6–9 mm size. 51% were left sided, 14% were right sided, location not specified in 35%, this difference was not statistically significant. Conclusion: In patients who are positive for FHH the incidence of diminutive polyps is considerable and importantly there is a significant proportion of adenomatous polyps. Based on these findings we believe that diminutive polyps should be resected, histologically evaluated and followed-up appropriately. Competing interests: None declared.